A portfolio of dilemmas: Experimental evidence on choice bracketing in a mini-trust game - Jieyao Ding (Max Planck Institute for Research on Collective Goods, 2012)
Bracketing is a mental procedure about how people deal with multiple tasks. If a decision maker handles all the tasks at the same time, it is called broad bracketing. If she handles the tasks separately, e.g., one or a few tasks each time, it is called narrow bracketing. This paper experimentally investigates the effect of broad versus narrow bracketing in the context of a mini-trust game. The result shows that, in the narrow bracketing treatment, the investor (first mover) is more likely to place trust on others, but the receiver (second mover) is less likely to fulfill the trust under the same condition. The effect is partly conditional on beliefs in others' behavior.
Keywords: C91; D03; 330; Framing; Choice Bracketing; Social Preference